Kolaborasi Pendampingan Pemasaran Produk Usaha Mikro Kecil (UMK) Berbasis Digital Marketing di Desa Jatimukti, kec. Jatinangor, kab. Sumedang, Jawa Barat - Astika athahirah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The increasingly rapid challenge of digitalization requires marketing of Micro, Small Enterprises (MSEs) products using various social media platforms or web-based platforms that can be accessed on each smartphone. However, there are still several obstacles faced in marketing MSE products, such as the lack of knowledge of MSEs in terms of proper marketing techniques, so digital marketing-based product marketing assistance is needed. This activity was carried out through collaborative activities between the author as a lecturer implementing community service and a marketing consultant in West Java. The aim of this activity is to maximize the digital marketing-based product marketing assistance process through several collaboration elements so that each MSEs actor can master the use of one or several platforms. This activity uses a Participatory Action Research (PAR) approach. The results show that all elements of collaboration can be fulfilled well, even though the time for implementing this activity is very short, the digital marketing-based product marketing assistance process continues to this day as a consultation forum for MSEs in Jatimukti Village, Jatinangor Subdisctrict.